Episode two: students, NFL: welcome back! - Tufts Daily (Tufts Archival Research Center, 2021)
Take Town is BACK for season 2! Aiden and Matt talk about the Fall return to sports, what this NFL season is going to look like, and explore what the heck this strange, strange time means for professional sports. Join us!